PENDIDIKAN ANTISIPATORIS DALAM PERSPEKTIF PENDIDIKAN ISLAM - Ridhwan M. Daud (FITRAH: International Islamic Education Journal, 2022)
Humans before birth have been equipped with various kinds of potential. If these potentials can be maintained and developed properly, humans will grow and develop perfectly and make them a resource to prosper this nature as God's purpose for creating humans themselves, namely as caliphs and servants of God on earth. In order to be able to continue or realize the caliphate and his servitude, humans in this family need to pay attention to certain things about their future children. In the pre-conception period, a man or woman must choose a future wife or husband from good people according to religious criteria, because the nature of a family will influence the character of the child to be born. In the pre-natal phase, a mother is advised to avoid bad deeds. Doing more good deeds such as attending recitation assemblies and reading the Koran is highly recommended. Besides that, pregnant women must also maintain food intake that meets food standards for pregnant women. This is important so that the mental and physical potential of the child to be born grows and develops perfectly. With the perfect growth and development of the two potentials, humans will be able to realize themselves as caliphs and servants of Allah on earth. The birth of weak, helpless children is something that must be avoided.